Higher Education - Smart, John C. (Springer, 2017)
Economic Models and Policy Analysis in Higher Education: A Diagrammatic Exposition -- Rankings and Classifications in Higher Education: A European Perspective -- Institutional Transformation and the Advancement of Women Faculty: The Case of Academic Science and Engineering...